Thalamo-cortical pain mechanisms - Lenz, Frederick (Henry Stewart Talks, 2009)
Areas of the brain stimulated by different kinds of pain stimuli, Mechanisms of activation in the thalamus and cortex, The spinothalamic tract, Physiological differences between different parts of the spinothalamic tract, Superficial dorsal horn, Response to temperature, Laminar 1 vs. deep laminar neurons of origin, Evidence against a separate thalamic nucleus specific to pain and thermal sensation, Activity in the thalamic relay to cortex, Single unit and microstimulation analysis of somatic sensory thalamus, Stimulus evoked spike trains composed of single spikes and bursts, Thalamocortical non-linearities, Thalamocortical circuitry, Binary, labelled non-linear and analog pathways traversing the thalamus: what are the cortical targets?, Transmission of visceral signals in the spinal cord, Effects of thalamic lesions, Distribution of LEPs, Is there nociceptive input to the cortical projection zones of nuclei?, BESA estimate of dipole location, Insular lesions may be associated with increased pain tolerance, ACC lesions are associated with increased gain of pain intensity and unpleasantness rating, Functional connectivity and networks, Synchrony assessed by phase locked value, Pre-stimulus synchrony predicts pain vs. non-painful sensations, Task-specific functional connectivity